WBMR: a new communication scheme for multicast routing in MANETs. (29th October 2019) - Nedumaran, Arappali; Jeyalakshmi, V.
There is a great demand for multicast route deployment and time varying link strategies which makes routing difficult in ad-hoc networks. Thus, finding the optimal routes with multicast behaviour in mobile ad hoc networks (MANETs) is a critical issue. The deployed route should fulfil the necessary requirements of MANET, like power utilisation, efficient utilisation of bandwidth, loop free communication, link stability and minimised usage of control overheads. Thus in research, the proposed Weight Based Multicast Routing (WBMR) protocol addresses the critical issues like loop free communication and link stability, which simultaneously yields the optimum routes and reduced energy utilisation of the nodes in MANETs. This proposition uses the weight based routing approach which is based on the distance and signal to noise ratio (SNR) of the demanding links. This WBMR protocol minimise the number of nodes participated in the communication in association with link stability and thus minimise the unnecessary utilisation of bandwidth and energy. The simulated results show that the implemented approach outperforms well when compared with the existing approaches in multicast routing schemes.